KARAKTERISASI IMPEDANSI LAPISAN TIPIS ZnS:Mn YANG DIBUAT DENGAN CO-EVAPORASI ZnS DAN Mn - Sahala S, Stepanus (Universitas Tanjungpura, 2014)
The aim of this research is to characterize impedance, capasitance and relative permitivity of the characteristics of electric thin film ZnS and ZnS:Mn. This research was started from making thin film with different deposition speed and with thermal co-evaporation method in vakum tubes.Â The estimation is the characteristics of thin film ZnS impedance and ZnS:Mn was done outside this vacum with various frequency between thousaund to million hertzs, with different deposition speed and the same thickness. Defining impedance of ZnS thin film wich the most optimal frequency would influence capasitance and relative permittivity of the thin film on the characteristics of the electricity. Besides, capasitance and resitance values of ZnS:Mn thin film would change if given different Mn portion on that thin film. From the result of the research, it could be identified as follows. On the area of the thousand to ten thousand Hertz, it was know is that relative permitivity/constante static dielectrics K(0) ZnS:Mn thin film was not the frequency function that it could be regarded as constant like K(o) = 10. The price of capasitance ZnS:Mn was increasing with less Mn amount in that thin film. The price of ZnS:Mn electric resitance is reduced with less Mn amount onÂ that thin film. Key words: Impedance, thin film ZnS:Mn, co-evaporation.